Issues On Financing The Growth Of Cooperatives In Malaysia: A Case Study On Capital Revolving Fund By Department Of Cooperatives Development Malaysia - A. Raman, Zainab (2008)
Cooperatives like any other business is directly tied to growth and profitability. The growth of cooperative is generated from their positive cash flow. A cooperative financial need will change over the lifetime of the business. Therefore, successful cooperatives understand that the business takes on different needs as it goes through its life cycle.